2012
DOI: 10.1590/s0034-89102011005000081
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Estratégia Saúde da Família na vigilância de óbitos infantis

Abstract: OBJECTIVE:To evaluate the effect of the Family Health Strategy on infant mortality surveillance. METHODS:An ecologic study was performed with a multiple group design, and the unit of analysis was municipalities in Bahia state (Northeastern Brazil) in 2008. The 3,947 deaths analyzed were obtained from the Mortality Information System, and the minimum acceptable level for death investigation was 25%. Logistic regression models were used for bivariate and multivariate analysis and adjusted for sociodemographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
4
0
11
Order By: Relevance
“…9 A committee to monitor mortality data a has been recently created to improve and regulate the flow of information. Commissions were also set up to investigate infant deaths in various municipalities, 14 contributing to improvements in data recording.…”
mentioning
confidence: 99%
“…9 A committee to monitor mortality data a has been recently created to improve and regulate the flow of information. Commissions were also set up to investigate infant deaths in various municipalities, 14 contributing to improvements in data recording.…”
mentioning
confidence: 99%
“…These are worrying problems, given that in the consultations the child has been suffering very serious consequences, interfering directly in their healthy growth. 17 Given the analysis of the data obtained in this integrative review, some difficulties were found in the application of IMCI, either in the structural aspect of the primary care network or because of lack of knowledge of the nurse in the protocol development. But, even with restrictions, it does not exempt the nurse from developing integrated child care.…”
Section: Resultsmentioning
confidence: 99%
“…The proactive search made it possible to identify problems in the implementation of vital information systems at the municipality level, to propose interventions to reduce local irregularities, and to develop a method to correct vital statistics in the 2000s. The investigation of death conditions among infants and the routine use of active search procedures by local health services, as recommended by the current health surveillance policies, should be implemented in problematic municipalities [12,36] to continue the process of reducing infant mortality in Brazil and to support pragmatic and viable alternatives in different social contexts.…”
Section: Resultsmentioning
confidence: 99%